2009
DOI: 10.1159/000200018
|View full text |Cite
|
Sign up to set email alerts
|

Plant Polyphenol Intake Alters Gene Expression in Canine Leukocytes

Abstract: Background/Aims: Polyphenol compounds may explain most of the health-related beneficial effects of plants and vegetables, mainly through their antioxidant properties. The aim of the study was to assess the main changes on leukocyte gene expression of dogs caused by intake of three natural polyphenol-rich extracts and to compare them with caloric restriction. Methods: 20 female dogs were divided into 5 groups: control fed ad libitum (C), caloric-restricted to 30% less than control (CR), and 3 groups fed ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…Our aim was to assess the safety of a polyphenol-rich extract from grape and blueberry (PEGB; from the Neurophenols Consortium) for dogs, by monitoring early biomarkers of renal damage over a 24-week period. This work considerably extends the previous study periods reported, where platelet effects, and gene expression profiles, were interrogated after 7 days, or 3 months of supplement use [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our aim was to assess the safety of a polyphenol-rich extract from grape and blueberry (PEGB; from the Neurophenols Consortium) for dogs, by monitoring early biomarkers of renal damage over a 24-week period. This work considerably extends the previous study periods reported, where platelet effects, and gene expression profiles, were interrogated after 7 days, or 3 months of supplement use [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 59%
“…The PEGB doses ranged from 4 to 40 mg/kg/d, the intentional dose for dogs facing cognitive decline being 4 mg/kg/d [as recommended by the Neurophenols Consortium]. In studies where dogs were fed supplements with grape seed/skin extract at 20 mg/kg/d [ 5 ], or grape seed proanthocyanidins at 5 mg/kg/d [ 6 ], symptoms related to acute renal failure were not reported. In the group given the PEGB at 4 mg/kg/d, the dose of grape extract was beneath these previously reported doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance between the production of free radicals and the ability of the body's antioxidant systems to eliminate them is known as oxidative stress. The inclusion of natural ingredients with antioxidant properties has been investigated in companion animals (Salas et al, 2008;Ogoshi et al, 2016), mainly because supplementation with synthetic antioxidants, such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA), has been perceived as unwanted by the owners. The present study evaluated the alterations of the oxidative stress markers in adult dogs fed with high levels of unsaturated fatty acids from the mixture of soybean oil enriched with DHA supplemented with natural algae-based antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus and Curcuma longa are known sources of polyphenols. In companion animals, citrus extract containing the polyphenols hesperidin and naringin has been shown to decrease plasma lipids and to have anti-inflammatory activity ( 4 , 5 ) . C. longa (turmeric) extracts, particularly the dietary polyphenol curcumin, have been shown to possess beneficial properties, especially anti-inflammatory properties ( 6 ) .…”
mentioning
confidence: 99%